The Effect of Long-Term External Counterpulsation Combined with Exercise Therapy on the Establishment of Collateral Circulation in Patients with Coronary Artery Occlusive Disease. (13th April 2022) - Du, Feng; Zhang, Wei; Mao, Hua; Guo, Yanli; Guo, Meiqin; Lu, Yuming; Chen, Min; Sha, Zhongxin
Abstract : Objective . By detecting the levels of external counterpulsation combined with exercise therapy on the levels of moesin, angiopoietin-like protein2 (Angptl 2), angiopoietin-like protein (Angptl 3), hypoxia inducible factor-1 α (HIF-1 α ), and RNA-34a (miR-34a) in patients with coronary artery occlusive disease, the effect of external counterpulsation combined with exercise therapy on the establishment of occluded coronary collateral circulation was studied. Methods . A retrospective analysis of 166 patients with coronary heart disease was confirmed by coronary angiography results that at least one coronary artery (anterior descending branch, circumflex branch, and right coronary artery) was completely occluded and was classified into the control group (routine medication) and the treatment group (routine drug therapy plus exercise therapy and external counterpulsation) according to the treatment plan of the patient. The serum levels of moesin, Angptl 2, Angptl 3, and HIF-1 α were detected by enzyme-linked immunosorbent assay (ELISA) test. The index of microcirculatory resistance (IMR) and coronary flow reserve (CFR) of the two groups of patients were measured before and after 2 weeks of treatment. The formation of collateral circulation was analyzed according to the Rentrop classification method. Results . After treatment, the IMR levels of the two groups were significantly decreased, and the CFR levels were significantly increased. The decrease of IMR level and the increase of CFR level in the experimental group were better than those in the control group (P < 0.05 ). There was no significant difference in the positive detection rate of moesin antibody between the two groups, but the OD detection value of the treatment group decreased significantly (P < 0.05 ). The levels of Angptl 2, Angptl 3, and miR-34a in the treatment group were lower than those in the control group, while the relative expression of HIF-1 α was higher than that in the control group. The difference was statistically significant (P < 0.05 ). External counterpulsation combined with exercise therapy improved the formation rate of collateral circulation (P < 0.05 ). Conclusions . External counterpulsation combined with exercise therapy can reduce moesin antibody, Angptl 2, Angptl 3, and miR-34a levels increase HIF-1 α levels, and promote the establishment of occluded coronary collateral circulation.